How we remember music tempo: the role of spontaneous motor tempo in recall and preference - Hine, Kyoko; Wakana, Yoshitomo; Nakauchi, Shigeki (Frontiers in Psychology, 2025)
Musical experiences—specifically in terms of how we prefer or remember them—differ among listeners, even when we listen to the same piece of music. Recent studies have suggested that spontaneous motor tempo (SMT), which refers to the pace of repeated body movements, predicts preferred music tempo. However, the question of whether SMT is related to recalled music tempo remains unanswered. We investigated whether SMT is related to recalled music tempo. The participants in this research performed three tasks—recall (no interval), recall (8-s interval), and preference—in which they adjusted music tempos under different conditions. SMT was assessed on the basis of a finger tapping task. Linear mixed models revealed that while the original music tempo predicted adjustments across tasks, SMT significantly predicted the adjusted tempo in the recall (8-s interval) and preference tasks but not in the recall task (no interval). These results suggest that the rehearsal of music tempo may be influenced by SMT.